Alive at the end of the world : poems - Jones, Saeed (Coffee House Press, 2022)
"Like his mentors, Patricia Smith and Rigoberto Gonzalez, Saeed writes poems that are lyrical, playful, musical, and political. It troubles expectations and asks the reader to challenge their assumptions about Blackness, sexuality, and socioeconomics. Saeed is responding here to white supremacy, heteronormativity, respectability politics, and the murders of Black people. In the service of equity and peace, Saeed elevates the matters that keep him up at night. If Prelude was a jettisoning of the oppressive structures Saeed experienced during his upbringing, ALIVE is a reminder that the work goes on, that freedom and equity are inextricably linked. In fact, a character from Prelude, known as Boy, carries through into ALIVE, which continues his work in Prelude with a maturity of perspective and more weariness. This is a work that examines the nuances of grief--the grief over lost family members and lost loves; the grief of white supremacy and the myth of safety from homophobia, anti-blackness, gun violence; the grief of covid"--